Susceptibility of clostridium difficile isolated from healthy captive asian elephants to metronidazole and vancomycin - Nattawooti Sthitmatee (2018)
Susceptibility to metronidazole and vancomycin, drugs of choice for Clostridium difficile infection, of 15 C. difficile isolates from 6 healthy Asian elephants was determined. All of the isolates belonged to only 1 ribotype pattern and carried both toxin A and B genes. The Minimal inhibitory concentration range of metronidazole and vancomycin, drugs of choice for treatment of C. difficile infection, was 0.125-4.0 μg/ml and 0.125-2.0 μg/ml, respectively. Moreover, MIC50 and MIC90 for metronidazole were 0.75 and 1.5 μg/ml while vancomycin was 1.0 and 2.0 μg/ml. There was no evidence of resistance to these antimicrobials. These results might be a preliminary data for further study of animal C. difficile.